Analysis of Impact and Sustainability in Chronic Diseases Prevention Program in XXX Highschool Balikpapan (Systematic Review) - Tarninda, Andi Amirul; Erwandi, Dadan (Syntax Corporation Indonesia, 2024)
A healthy lifestyle requires discipline. It's not easy, particularly adolescent who feel free and are looking for their existence. Its implementaiton needs to be applied to adolescent due to many cases of chronic diseases developing among them, following their lifestyle. Sedentary/lazy to move, smoking, alcohol, lack of rest and not being able to manage mental health. Generally, adolesecent at the educational level of Junior and Senior High School. The objective of this study is to analyze aspects of the impact and sustainability of chronic disease prevention programs for adolescents. This study is a systematic review using the PRISMA (Preferred Reporting Items for Systematic Reviews & Meta Analyses) method combined with open-source search engine. The database used for searching data and information is PubMed. The keywords used during the search process are